Tourism Development in Improving Community Welfare in West Lombok Regency - Amil Amil; Nurul Hidayati Indra Ningsih; Asbur Hidayat (International Journal of Halal System and Sustainability, 2021)
The West Lombok is a tourist destination area in the West Nusa Tenggara Province, which has a strategic role as a tourist destination. This study aims to gain an overview of the effects of tourism growth in the West Lombok Regency, West Nusa Tenggara, on improving community welfare. Techniques for the processing data are interviews, observation and documentation. The results showed that after the 2018 earthquake, tourism growth in West Lombok was getting better with the availability of different types of support facilities at tourist attractions. The growth of tourism has had an impact on shifting the livelihoods of people from the agricultural sector to the service sector, such as transport services and tour guides. In addition, the growth of the trade sector and the home industry, such as stores, stalls, beverage stalls, hawkers, street vendors, and different kinds of art shops, but the revenue they earn is still very far from the expectations they want because they lose competitiveness with entrepreneurs with capital that causes traders to raise the price of goods to increase revenue, high prices have an effect on visitors who prefer shopping outside tourist attractions because of lower prices, they prefer luxury shops if they shop at tourist attractions so that people's wellbeing does not increase.